Pengaruh Self Efficacy dan Self Esteem Terhadap Prestasi Akademik Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang - Fadhil Subandrio; Suhana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted at Stikubank University Semarang at the Faculty of Economics and Business. This research aims to analyze the influence of self-efficacy and self-esteem on student academic achievement. This research has a population of 1,160 students registered at the faculty of economics and business. The sampling technique uses a non-probability sampling method with a purposive sampling technique with criteria for students from semester 4 to semester 8. The number of samples in this research is 100 respondents. The results of this research shows that self-efficacy has a positive and significant effect on student academic achievement, self-esteem has a positive and significant effect on student academic achievement.